Our country's Presidents : all you need to know about the presidents, from George Washington to Barack Obama - Bausum, Ann; Obama, Barack; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2009)
Complete with period paintings and photos, a comprehensive guide provides profiles, biographies, administration highlights, and political and personal accomplishments of every president in the history of the United States, along with a review of Air Force One, the Secret Service, and a look at the various Presidential retreats
"Featuring the 2008 election"--Spine
Includes bibliographical references (p. 213-214) and index
Keywords: Presidents -- Biography